cGAS/STING signaling pathway in gynecological malignancies: From molecular mechanisms to therapeutic values - Danyang Zhang; Bingxue Zhang (Frontiers in Immunology)
Gynecological cancers, including cervical, ovarian, and endometrial malignancies, remain a significant global health burden, exacerbated by disparities in access to preventive measures such as HPV vaccination and routine screening. The cGAS/STING signaling pathway, a pivotal mechanism in innate immunity, detects cytosolic DNA from pathogens or cellular damage, triggering immune responses via type I interferons and inflammatory cytokines. This pathway’s dual role in gynecological cancers, either promoting antitumor immunity or facilitating tumor immune evasion, makes it a compelling target for innovative therapies. The article outlines cGAS/STING’s influence on tumor microenvironments, immune surveillance, and inflammation, with emphasis on molecular mechanisms driving cancer progression. It explores interactions between DNA damage response pathways and immune modulation, highlighting the impact of cGAS/STING activation or suppression in ovarian, cervical, and endometrial cancers. The therapeutic potential of STING agonists, PARP inhibitors, and targeted immunotherapies is reviewed, demonstrating how these approaches can boost immune responses, counteract chemotherapy resistance, and improve patient outcomes. The study also discusses strategies for leveraging cGAS/STING signaling to enhance the efficacy of immunotherapies and address tumor-mediated immune suppression, providing insights into future directions for personalized cancer treatments.